Effect of Administration of Phaleria Macrocarpa on Liver Function of Nasopharyngeal Carcinoma Patients who Receive Cisplatin Chemotherapy - Akbar, Adi Januar; Yusmawan, Willy; Farokah, Farokah; Nugroho, Nur Iman (Indonesian Journal of Medicine, 2022)
Background: Nasopharyngeal cancer (NPC) is a malignant tumor located in the nasopharynx, which can be treated by Cisplatin, a chemotherapy that has a side effect of increasing the production of Reactive Oxygen Species (ROS) that can damage the liver. We aim to determine the effect of giving Mahkota Dewa (Phaleria macrocarpa) as an antioxidant on liver function of NPC patients receiving Cisplatin chemotherapy. Subjects and Method: Forty subjects of stage III and IV Nasopharyngeal Carcinoma patients were divided into treatment and control groups. Subjects will be tested for SGOT SGPT before cisplatin chemotherapy. The treatment group was given Phaleria macrocarpa capsules 300 mg/24 hours for 5 weeks since a week before chemotherapy. The control group was given placebo capsules/24 hours for 5 weeks since a week before chemotherapy. The patients received two series of cisplatin chemotherapy with an interval of 3 weeks, then a second blood sample was taken 1 week after the second series of cisplatin chemotherapy.Results: There was a significant difference in SGOT levels in the post-treatment group of Phaleria macrocarpa and control, as well as the difference in the pre- and post- treatment group between the Phaleria macrocarpa and control groups. Also, there was a significant difference in SGPT levels in the pre- and post- treatment in the Phaleria macrocarpa and control groups.Conclusion: The administration of Phaleria macrocarpa has an effect on decreasing the levels of SGOT and SGPT in NPC patients receiving Cisplatin chemotherapy therapyKeywords: Phaleria macrocarpa, SGOT, SGPT, Nasopharyngeal Carcinoma, CisplatinCorrespondence: Adi Januar Akbar. ENT Department of Diponegoro University. Prof. Sudarto Street No. 13, Tembalang, Tembalang Sub-district, Semarang City, Central Java, 50275. Email: diaz17akbarsaleh@gmail.com. +628161455179.Indonesian Journal of Medicine (2022), 07(01): 1-8https://doi.org/10.26911/theijmed.2022.07.01.01